Following the Fate of Bacterial Cells Experiencing Sudden Chromosome Loss - Elbaz, Maya (mBio, 2015)
Chromosomal DNA is a constant source of information, essential for any given cell to respond and adapt to changing conditions. Here, we investigated the fate of exponentially growing bacterial cells experiencing a sudden and rapid loss of their entire chromosome. Utilizing Bacillus subtilis cells harboring an inducible copy of the endogenous toxin yqcG, which encodes an endonuclease, we induced the formation of a population of cells that lost their genetic information simultaneously. Surprisingly, these DNA-less cells, termed DLCs, did not lyse immediately and exhibited normal cellular morphology for a period of at least 5 h after DNA loss. This cellular integrity was manifested by their capacity to maintain an intact membrane and membrane potential and cell wall architecture similar to those of wild-type cells. Unlike growing cells that exhibit a dynamic profile of macromolecules, DLCs displayed steady protein and RNA reservoirs. Remarkably, following DLCs by time lapse microscopy revealed that they succeeded in synthesizing proteins, elongating, and dividing, apparently forming de novo Z rings at the midcell position. Taken together, the persistence of key cellular events in DLCs indicates that the information to carry out lengthy processes is harbored within the remaining molecular components.